The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/agr.21762
|View full text |Cite
|
Sign up to set email alerts
|

Toward a differentiated understanding of the effect of Nutri‐Score nutrition labeling on healthier food choices

Abstract: By 2022, the European Commission seeks to introduce harmonized, mandatory front-of-pack (FOP) nutrition labeling. The color-graded Nutri-Score is at the heart of the European debate. Yet, little is known about how the information provided in back-of-pack (BOP) nutrition tables interacts with evaluative FOP labels, such as Nutri-Score,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have shown that displaying the Nutri-Score on product packaging allows (1) better knowledge of the global nutritional quality of foods and healthier food choices [ 10 15 ] and (2) to limit the potential halo effects on health of nutritional claims about added sugars promoted by companies on packaging (for example, 30% less sugar) which may make products appear healthier than they really are [ 27 ]. The present study extends these results by showing the existence of effects of the Nutri-Score on cognitive judgments related to perceptions of nutritional quality and more or less favorable health-promoting effects of food products, in the context of advertising.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that displaying the Nutri-Score on product packaging allows (1) better knowledge of the global nutritional quality of foods and healthier food choices [ 10 15 ] and (2) to limit the potential halo effects on health of nutritional claims about added sugars promoted by companies on packaging (for example, 30% less sugar) which may make products appear healthier than they really are [ 27 ]. The present study extends these results by showing the existence of effects of the Nutri-Score on cognitive judgments related to perceptions of nutritional quality and more or less favorable health-promoting effects of food products, in the context of advertising.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that front-of-pack labeling (FoPL) and, in particular, the Nutri-Score can help consumers identify the nutritional quality of products [ 10 , 11 ]. It then influences food choices by directing them towards healthier products [ 12 15 ]. Thus, as the Nutri-Score can effectively and quickly inform about the overall nutritional quality of foods, displaying it in advertising messages could reduce the deleterious effects of advertising for HFSS products.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, for example, in the dairy products group, 15.3% of foods were classified with Nutri-Score A and NOVA 4, and only 1.1% were classified with Nutri-Score A and NOVA 1. Generally, food products rated as Nutri-Score A or B are perceived as healthier, increasing purchase intentions [ 45 , 46 ]. Thus, regardless of other individual determinants, if information on other dimensions of food is not provided, consumers may base their food choices mainly on the nutritional quality of food.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, food manufacturers tend to reformulate their products to attain a better Nutri-Score by reducing the sugar, fat, and salt content or increasing the amount of fibre to capture consumers, regardless of the degree and extent of processing this reformulation requires [ 46 ]. A study carried out in France by Union Fédéral des Consommateurs (UFC-Que Choisir) showed that between 2015 and 2022, the nutritional quality improved in three of the seven food groups analyzed and in which Nutri-Score is more frequently displayed, namely in cereal bars, special breads and rusk, and breakfast cereals.…”
Section: Discussionmentioning
confidence: 99%
“…48,80,81,[87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105] advertising and prevention of childhood obesity in Spain: Analysis of the nutritional value of the products and discursive strategies used in the ads most viewed by children from 2016 to 2018[70] Soft drinks and sugar-sweetened beverages advertising in Spain: Correlation between nutritional values and advertising discursive strategies[65] Breakfast food advertising and prevention of obesity: Analysis of the nutritional value of the products and discursive strategies used in the breakfast ads from 2015…”
mentioning
confidence: 99%